Weed Management in Conservation Agriculture Systems - A. R. Sharma; V. P. Singh (International Journal of Economic Plants)
Adequate food production for ever-increasing global population can only be achieved through the implementation of sustainable growing practices that minimize environmental degradation and preserve resources while maintaining high-yielding profitable systems. Conservation agriculture practices are designed to achieve agricultural sustainability by implementation of sustainable management practices that minimize environmental degradation and conserve resources. Weeds are the major constraints in CA-based systems. Tillage affects weeds by uprooting, dismembering, and burying them deep enough to prevent emergence, by moving their seeds both vertically and horizontally, and by changing the soil environment and so promoting or inhibiting weed seed germination and emergence. Still There is a need to gain understanding on weed management as it is the major hindrance in CA-based crop production systems. Weed control in CA is a greater challenge than in conventional agriculture because there is no weed seed burial by tillage operations. Preventive measures are first and the most important steps to be taken to manage weeds in general and especially under CA as the presence of even a small quantity of weed seeds may cause a serious infestation in the forthcoming seasons. Considering the diversity of weed problems, no single method of weed control, viz. cultural, mechanical or chemical, could provide the desired level of weed control efficiency under CA. Therefore, a combination of different weed management strategies should be evaluated for widening the weed control spectrum and efficacy for sustainable crop production.